The Learner’s Voice: A Focus on the e-learner Experience - Creanor, Linda; Gowan, Doug; Howells, Carol; Trinder, Kathy (Proceedings of the International Conference on Networked Learning, 2006)
This paper outlines work in progress on a national JISC research project on the learner experience of e-learning. The project is named LEX, a contraction of the long name but also a reference to the importance of using the learner’s own words in the analysis. The project covers a wide range of post-16 learners including adult, community and work-based learners as well as FE and HE learners, distributed widely across the UK. We describe the development, evolution and implementation of the research methodology, and how we tackled practical problems of reaching such a diverse learner group. We go on to outline three case studies which illustrate how learners describe their approaches to fitting learning into their lives, to accomplishing e-learning tasks, their strategies to overcome problems, and their expectations and experiences of e-learning across a range of educational contexts and technology use. The paper does not present findings or research outcomes, however tentative, since we are only at the start of the analytical phase. The case studies do however indicate some of the issues that learners have raised in the research.